1984
DOI: 10.1007/bf02403250
|View full text |Cite
|
Sign up to set email alerts
|

Structure of special grain boundaries in SiAlON ceramics

Abstract: The microstructure of hot-pressed samples of the 15 R polytype phase in the Si-AI-O-N system was studied by means of TEM. Emphasis was put on studies of high angle grain boundaries. In this material high angle boundaries of arbitrary orientation usually possess a vitreous grain boundary phase. However, special grain boundaries were found, which were free of any vitreous grain boundary phase. From the orientation relation of the adjacent grains 2; = 1 (coherent reflection twin boundary), 2; = 7 and 2; = 13 boun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

1987
1987
2008
2008

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(7 citation statements)
references
References 24 publications
(30 reference statements)
0
7
0
Order By: Relevance
“…Instead, they solidify as a thin amorphous film between adjoining crystalline phases at both grain and phase boundaries. The thickness of these films is normally on the order of 1-2 nm, [5][6][7][8] with the exception of homophase low-angle and twin boundaries that are free of glass, 9 similar to earlier interface studies on BeSiN ceramics. 10 However, siliceous thin films wetting internal interfaces have been found to exist basically in all Si 3 N 4 and SiAlON systems 9,[11][12][13][14] and their thickness was reported to be rather insensitive to the volume fraction of residual glass.…”
Section: Introductionmentioning
confidence: 61%
“…Instead, they solidify as a thin amorphous film between adjoining crystalline phases at both grain and phase boundaries. The thickness of these films is normally on the order of 1-2 nm, [5][6][7][8] with the exception of homophase low-angle and twin boundaries that are free of glass, 9 similar to earlier interface studies on BeSiN ceramics. 10 However, siliceous thin films wetting internal interfaces have been found to exist basically in all Si 3 N 4 and SiAlON systems 9,[11][12][13][14] and their thickness was reported to be rather insensitive to the volume fraction of residual glass.…”
Section: Introductionmentioning
confidence: 61%
“…32 Intergranular film thickness and chemistry in Si 3 N 4 and SiAlONs have been studied extensively by high resolution and analytical electron microscopy. Schmid and Rühle 33 reported that wetting of grain boundaries in SiAlONs is dependent on the degree of misorientation between the grains, with some low-angle and twin boundaries being free of the intergranular phase. A recent paper by Gu 34 introduced data showing that intergranular film thickness and chemistry are dependent on the level of impurities in the material.…”
Section: Intergranular Phasesmentioning
confidence: 99%
“…This circumstance makes it easier to model these wetted grain-boundary structures, as compared to directly bonded (e.g., oxide) ceramics, whose grain-boundary structure markedly depends on the misfit angle between neighboring crystals. 7,8 In recent studies, 9 -15 we have examined the possibility of using the internal friction technique to quantitatively evaluate the intrinsic viscosity of residual glasses segregated at grain boundaries of polycrystalline ceramics. Our investigations are based on the original idea proposed by Mosher and co-workers, 16,17 who used the Zener relaxation mechanism 18 to evaluate the rate of grainboundary sliding in Si 3 N 4 ceramics.…”
Section: Introductionmentioning
confidence: 99%